Low-electric-potential-assisted diffusiophoresis for continuous separation of nanoparticles on a chip. Issue 15 (29th June 2020) - Lee, Kyunghun; Lee, Jongwan; Ha, Dogyeong; Kim, Minseok; Kim, Taesung
Abstract : We developed a novel multiphysics-based nanoparticle separation technique utilizing low-electric-potential-assisted diffusiophoresis (LEPDP). Abstract : Nanoparticle separation techniques are of significant importance in nanoscience and nanotechnological applications and different concentration gradients, electric/dielectric forces, flow/pressure fields, and acoustic waves have been intensively investigated. However, precise separation of nanoparticles has many technical challenges in terms of sizes, shapes, and material properties, limiting the separation resolution, capability, applicability, throughput and so on. In this study, we present a microfluidic device for continuous separation of nanoparticles by combining diffusiophoresis (DP) and electrophoresis (EP) to achieve high separation performance. Concentration gradients formed from sodium chloride (NaCl) and potassium acetate (K-acetate) passively drive the diffusiophoretic migration of nanoparticles. Simultaneously, a low electric potential is additionally applied to impose a synergistic effect on nanoparticle migration by size and surface charge, which is called low-electric-potential-assisted DP (LEPDP). Using a LEPDP-based separation device, we demonstrate the separation of nanoparticles having different sizes (diameters of 500, 200, and 50 nm) and under different surface-charge conditions (carboxylated polystyrene, silica, and polylactide). The resulting separation performance exceeded 95%, in terms of size uniformity, which is about two times better than that obtained using DP alone. We also emphasize that the enhancement of separation performance only needs a small voltage (<1 V), thereby demonstrating that our multiphysical approach could be utilized for high-resolution and portable nanoparticle separation on a chip without the side effects associated with high electric fields. Lastly, we ensure that rapid and precise bio/chemical sensing and analysis of various nanosized particles would be envisioned by strategically combining two nonlinear but synergistic migration effects.